Basic isoreticular metal–organic framework (IRMOF‐3) porous nanomaterial as a suitable and green catalyst for selective unsymmetrical Hantzsch coupling reaction. (14th April 2014) - Rostamnia, Sadegh; Xin, Hongchuan
<x xml:space="preserve">Abstract</x> A catalytic amount of the basic metal–organic framework (IRMOF‐3) with organic substrates was found to be an efficient, selective and waste‐free green approach for the unsymmetrical Hantzsch coupling reaction. The catalyst can be isolated from the reaction mixture and reused at least four times. Copyright © 2014 John Wiley & Sons, Ltd.